2016
DOI: 10.7196/samj.2016.v106i11.12065
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the intergenerational transmission of violence

Abstract: Intimate partner violence is a major public health and human rights issue in South Africa. This violence tends to run in families and generations, with little change over time and devastating consequences at individual, family and community levels. Understanding the mecha nisms for intergenerational transmission of violence may offer important clues for prevention and intervention to halt this recurrence. Health professionals are well placed to identify patients at risk and intervene in families characterised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…A common approach is to focus on the role of family conflict [22]. We have learned, for example, that individuals who report child abuse are much more likely to perpetrate IPV [23,24]. Likewise, a 2018 review found that children who witness parental IPV were up to four-fold more likely to perpetrate IPV as adults [25].…”
Section: Introductionmentioning
confidence: 99%
“…A common approach is to focus on the role of family conflict [22]. We have learned, for example, that individuals who report child abuse are much more likely to perpetrate IPV [23,24]. Likewise, a 2018 review found that children who witness parental IPV were up to four-fold more likely to perpetrate IPV as adults [25].…”
Section: Introductionmentioning
confidence: 99%
“…This includes but not limited to homicide [ 15 , 16 ], suicide attempts [ 17 ], poor mental health [ 18 ], and several adverse reproductive health outcomes such as pregnancy termination [ 19 ], gynaecologic morbidities [ 20 ], and posttraumatic stress disorders [ 21 ]. IPV is thus a public health and human right crisis across the world [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo, en una de las sentencias analizadas se exponía lo siguiente "/…/ estos episodios violentos, en especial los insultos y menosprecios, ocurrieron alguna vez en presencia del hijo menor /…/ que también fue golpeado por el acusado en varias ocasiones" (Sentencia 34). Al hilo de la presencia de los niños, una cuestión que habría que cuidar es la transmisión intergeneracional de la violencia, es decir cómo evitar o reducir el daño en estos niños y niñas para que en el futuro sus relaciones de pareja y familiares sean saludables y de buen trato 49,50,51,52,53 .…”
Section: Los Hijos Como Guardianes Ante Las Agresiones Dirigidas a Suunclassified